Spatial river water quality assessment in Tanjung Malim, Perak (Malaysia) using multivariate statistical analysis - Mohammed Kadhem Abid (Tanjong Malim, 2019)
Spatial river water quality assessment in Tanjung Malim, Perak (Malaysia) using multivariate statistical analysis by Mohammed Kadhem Abid